Sinusoidal Optic Flow Perturbations Reduce Transient but Not Continuous Postural Stability: A Virtual Reality-Based Study - Ketterer, Jakob; Ringhof, Steffen; Gehring, Dominic; Gollhofer, Albert (Frontiers in Physiology, 2022)
Optic flow perturbations induced by virtual reality (VR) are increasingly used in the rehabili-tation of postural control and gait. Here, VR offers the possibility to decouple the visual from the somatosensory and vestibular system. By this means, it enables training under conflicting sensorimotor stimulation that creates additional demands on sensory reweighting and bal-ance control. Even though current VR-interventions still lack a well-defined standardized metric to generate optic flow perturbations that can challenge balance in a repeatable manner, continuous oscillations of the VR are typically used as a rehabilitation tool. We therefore studied continuous sensory conflicts induced by optic flow perturbations regarding their ability to challenge the postural system sustainably. Eighteen young adults were re-cruited for the study. The VR was provided using a state-of-the-art head-mounted display including the virtual replica of the real environment. After familiarization in quite stance without and with VR, bipedal balance was perturbed by sinusoidal rotations of the visual scenery in the sagittal plane with an amplitude of 8 degrees and a frequency of 0.2 Hz. Pos-tural stability was quantified by mean center of mass velocity derived from 3D-kinematics. A rmANOVA found increased postural instabilSity only during the first perturbation cycle, i.e., the first 5 seconds. Succeeding the first perturbation cycle, visual afferents were downregu-lated to reduce the destabilizing influence of the sensory conflicts. In essence, only the tran-sient beginning of sinusoidal oscillation alters balance compared to quite standing. Our study therefore questions the use of continuous optic flow perturbations for balance training and provides rationale for using unexpected and discrete optic flow perturbation paradigms to induce sustainable sensory conflicts.